Running With the Dead: Speedruns and Generative Rupture in Left 4 Dead 1 and 2. Issue 5 (July 2020) - McKissack, Fraser; May, Lawrence
Distinctive narrative conditions arise when "speedrunning" the zombie narrative in Valve Corporation's cooperative first-person shooter games Left 4 Dead (2008) and Left 4 Dead 2 (2009). Close analyses of two live speedruns recorded at the biannual Games Done Quick charity marathon, guided by concepts from Deleuze and Guattari, explain how the player's narrative body, space, and time are impacted by the optimizations and exploits of the Left 4 Dead series' zombie narrative. While the zombie story preprogrammed for players is largely bypassed, speedrunning through the Left 4 Dead series' environments is a generative act of rupture that activates and deepens storytelling tendencies within zombie media that embrace chaos and decay. The speedrun is itself a form of collapse, where scripted meaning and intentionality fall away, replaced by the chance and ephemeral story of an emergent, optimized engagement.